KNOWLEDGE REGARDING MODE OF DELIVERY IN PRIMARY GRAVIDA WOMEN - BOOTA , F; LIAQAT, R; SADDIQUE, H; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
In Pakistan, childbirth knowledge among primary gravida women—those experiencing pregnancy for the first time—plays a crucial role in shaping their decisions regarding the mode of delivery. Misconceptions, cultural beliefs, and social pressures significantly influence these women’s preferences, often leading to an increased rate of elective caesarean sections (CS) without medical necessity. Understanding the knowledge level regarding delivery options in this population is essential to improve maternal and neonatal outcomes. Objective: This study aimed to assess the level of knowledge regarding the mode of delivery among primary gravida women attending antenatal care at Jinnah Hospital, Lahore, and to identify gaps that may influence their decision-making. Methods: A descriptive cross-sectional study design was employed, targeting 150 primary gravida women at Jinnah Hospital, Lahore. A purposive sampling technique was used, and data were collected using a structured questionnaire comprising demographic questions and items related to knowledge and perceptions of vaginal and caesarean deliveries. Data were analyzed using SPSS version 22, with descriptive statistics used to summarize findings. The questionnaire’s reliability was confirmed with a Cronbach’s Alpha of 0.986, and validity was established through the Kaiser-Meyer-Olkin (KMO) measure and Bartlett’s Test of Sphericity. Results: The findings indicated that 34.7% of participants had poor knowledge regarding the mode of delivery, 62.0% had moderate knowledge, and only 3.3% demonstrated good knowledge. Most participants preferred CS due to fear of labor pain and misconceptions about vaginal delivery risks. A majority (90%) of respondents viewed seeing the baby immediately after vaginal delivery positively, and 44% believed that the emotional relationship with the baby is enhanced following vaginal delivery. Informal sources, primarily relatives and friends, were the main sources of delivery-related information, contributing to persistent knowledge gaps and misconceptions. Conclusion: The study reveals significant knowledge gaps among primary gravida women regarding delivery options in Pakistan, with many women favoring CS due to fear and lack of accurate information. Structured antenatal education programs are necessary to address misconceptions and empower women to make informed decisions about their delivery mode. Improved education could reduce unnecessary CS rates and support healthier maternal and neonatal outcomes.